Microbial production of poly (3-hydroxybutyrate) (PHB) from rubber seed oil using Cupriavidus necator H16 - Reddy Prasad, D.M. (Institute of Physics Publishing, 2019)
Rubber seed oil is inedible plant oil that is a potential replacement for the traditional organic building blocks used in PHB biosynthesis. Herein we describe the biosynthesis of PHB by Cupriavidus necator H16 grown in media with rubber seed oil and urea serving as carbon and nitrogen sources, respectively. The method was optimized over a temperature range of 30-50 °C for batch culture studies. A maximized PHB concentration of 15.4 g/L, and dry well weight of 19.2 g/L was obtained using 20 g/L of rubber seed oil at 30°C. Experimental results were used to generate a logistic curve, and the Luedeking-Piret model was implemented to predict the specific growth rate of C. necator at 0.1898 1/h. The estimated rate constants were in good agreement with experimental values. This study demonstrated that rubber seed oil is a viable alternative to conventional carbon sources for the production of PHB using C.necator H16. © 2019 Published under licence by IOP Publishing Ltd.